Internship report on roles of digital marketing communications over conventional marketing: a prospective on Solution Hub Advertising Agency - Zaman, Noor – A – Mehide (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.